Substrate-mediated effects in photothermal patterning of alkanethiol self-assembled monolayers with microfocused continuous-wave lasers - Schröter, Anja; Kalus, Mark; Hartmann, Nils (Beilstein Journal of Nanotechnology, 2012)
In recent years, self-assembled monolayers (SAMs) have been demonstrated to provide promising new approaches to nonlinear laser processing. Most notably, because of their ultrathin nature, indirect excitation mechanisms can be exploited in order to fabricate subwavelength structures. In photothermal processing, for example, microfocused lasers are used to locally heat the substrate surface and initiate desorption or decomposition of the coating. Because of the strongly temperature-dependent desorption kinetics, the overall process is highly nonlinear in the applied laser power. For this reason, subwavelength patterning is feasible employing ordinary continuous-wave lasers. The lateral resolution, generally, depends on both the type of the organic monolayer and the nature of the substrate. In previous studies we reported on photothermal patterning of distinct types of SAMs on Si supports. In this contribution, a systematic study on the impact of the substrate is presented. Alkanethiol SAMs on Au-coated glass and silicon substrates were patterned by using a microfocused laser beam at a wavelength of 532 nm. Temperature calculations and thermokinetic simulations were carried out in order to clarify the processes that determine the performance of the patterning technique. Because of the strongly temperature-dependent thermal conductivity of Si, surface-temperature profiles on Au/Si substrates are very narrow ensuring a particularly high lateral resolution. At a 1/e spot diameter of 2 µm, fabrication of subwavelength structures with diameters of 300–400 nm is feasible. Rapid heat dissipation, though, requires high laser powers. In contrast, patterning of SAMs on Au/glass substrates is strongly affected by the largely distinct heat conduction within the Au film and in the glass support. This results in broad surface temperature profiles. Hence, minimum structure sizes are larger when compared with respective values on Au/Si substrates. The required laser powers, though, are more than one order of magnitude lower. Also, the laser power needed for patterning decreases with decreasing Au layer thickness. These results demonstrate the impact of the substrate on the overall patterning process and provide new perspectives in photothermal laser patterning of ultrathin organic coatings.
Keywords: femtosecond lasers; nonlinear laser processing; self-assembled monolayers; subwavelength patterning; ultrathin resists